From tin oxalate to (Fe, Co, Nb)-doped SnO(2): Sintering behavior, microstructural and electrical features - Parra, R. [UNESP]; Ramajo, L. A.; Goes, M. S. [UNESP]; Varela, José Arana [UNESP]; Castro, M. S. (Pergamon-Elsevier B.V. Ltd, 2008)
Highly reactive SnO(2)-doped nanocrystalline powders with average particle size of 20 nm and specific surface areas above 30 m(2)/g were obtained through the polymeric precursor method with tin oxalate (SnC(2)O(4)) as a chloride-free precursor for SnO(2). Powder, and sintered discs were characterized by means of X-ray powder diffraction (XRD), SEM and TEM. The influence of Co and Fe on the microstructure development and on the electrical properties of dense SnO(2)-based ceramics was studied. Co and Fe species were found to decrease in more than 70 degrees C the sintering temperature of SnO(2) with respect to mixed oxide procedures. Secondary phases enriched in Co and Fe were detected and identified in sintered samples with XRD. Current-voltage curves were registered for electrical characterization. Doping with iron increased the electrical breakdown field and a nonlinearity coefficient of 20 was achieved. (c) 2008 Elsevier Ltd. All rights reserved.
Keywords: Ceramics; Semiconductors; Chemical synthesis; Defects; Electrical properties